PENGARUH PEMBERIAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN TETAP PADA PT. KHARISMA PEMASARAN BERSAMA NUSANTARA UNIT DUMAI - Tuntun Elisabeth Pasaribu; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of compensation and work environment partially and simultaneously. This study used a questionnaire as a data collection tool which was distributed to 50 respondents to permanent employees at PT. Kharisma Pemasaran Bersama Nusantara Dumai Unit. The data is then processed using descriptive analysis and statistical analysis using SPSS 26.0 by conducting validity tests, reliability tests, classical assumption tests, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and hypothesis testing with t test testing (partial) and F test (simultaneous). The results showed that the first hypothesis testing, namely the provision of compensation has a positive effect on job satisfaction. Testing the second hypothesis that the work environment has a positive effect on job satisfaction. The results of the F test that the provision of compensation and the work environment simultaneously have a positive effect on employee job satisfaction Keywords: Compensation, Work Environment, Job Satisfaction